Analisis Potensi Kawasan Resapan Air Pada DAS Batang Pasaman Kabupaten Pasaman Barat - W, israningtyas (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to: 1) determine the area that has the potential to become a water catchment area in the Batang Pasaman watershed area, 2) find out changes in land cover in the Batang Pasaman watershed catchment area in 2011-2019, 3) find out the index of potential water catchment based on land cover in the watershed. Pasaman Trunk. This research is classified as quantitative research, the analysis technique in this study uses the overlay and matching methods. The results of the study are: 1) The results of the identification of the determination of the potential for water catchment areas indicate that there are 4 areas dominated by cultivation areas (35.04%) and primary catchment areas (31.56%). 2) land cover changes that occur in primary catchment areas are 16.10%, low potential water catchment areas are 54.44%, and high potential water catchment areas are 21.83%. 3) processing the water absorption potential index based on land cover shows that there are 4 classifications dominated by the